Ideas across time : (McGraw Hill, 2008)
Ideas Across Time gives depth to students' writing by helping them make connections between their contemporary world and the important ideas that have shaped it. Beginning with a contemporary selection that ties the chapter's idea to the student's experience, each chapter proceeds to introduce students to significant and influential writers and thinkers. Thoughtful and provoking reading apparatus helps students understand challenging concepts, encourages them to develop ideas in their writing, and prompts them to research new questions.